Stabilization of metal(loid)s in two contaminated agricultural soils: Comparing biochar to its non-pyrolysed source material. (August 2017) - Trakal, Lukáš; Raya-Moreno, Irene; Mitchell, Kerry; Beesley, Luke
Abstract: Two metal(loid) contaminated agricultural soils were amended with grape stalk (wine production by-product)-derived biochar as well as its pre-pyrolysed origin material, to investigate their geochemical impacts on As, Cr, Cu and Zn. Detailed physico-chemical evaluation combined with a column leaching test determined the retention of metal(loid)s from soil solution by each amendments. A pot experiment measured metal(loid)s in soil pore water and their uptake to ryegrass when the amendments were mixed into soils at 1 and 5% (w/w). Total Cr and Zn concentrations were reduced furthest in column leachates by the addition of raw material and biochar respectively, compared to the untreated soil; Cr(III) was the predominant specie initially due to rapid acidification of leachates and organic complexation resulting from raw material addition. Loadings of metal(loid)s to the amendments recovered from the post-leached columns were in the order Cu » Zn > Cr ≈ As. In the pot test ryegrass Cr uptake was initiated by the addition of both amendments, compared to the untreated soil, whereas only biochar addition resulted in significant increases in Zn uptake, explained by its significant enhancement of ryegrass biomass yield, especially at 5% dosage; raw material addition significantly decreased biomass yields. Inconsistent relationships between pore water parameters and ryegrass uptake were common to both soils investigated. Therefore, whilst both amendments modified soil metal(loid) geochemistry, their effects differed fundamentally; in environmental risk management terms these results highlight the need to investigate the detailed geochemical response of contaminated soils to diverse organic amendment additions. Graphical abstract: Highlights: Biochar and its source material stabilized various metal(loid)s in the soils. Original grape stalks can effectively reduce Cr(VI) to Cr(III). Biochar was the more stable material with high reactive surface. Source material generated higher DOC concentrations and acidic pH in the pore water. Source material significantly decreased ryegrass yield in comparison to biochar.